2020
DOI: 10.3390/foods10010058
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Prunus mume Fermented with Mixed Lactic Acid Bacteria in Dextran Sodium Sulfate-Induced Colitis

Abstract: The fruit of Prunus mume (PM) is widely cultivated in East Asia, and it has been used as a folk medication for gastrointestinal disorders, e.g., diarrhea, stomach ache and ulceration. In this study, the pectinase-treated PM juice (PJ) was fermented with Lactobacillus strains containing fundamental organic acids and free amino acids. The PJ fermented with Lactobacillus plantarum and L. casei (FP) was investigated for its protective effect in dextran sodium sulfate (DSS)-induced colitis mice model. The administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…CD is dominated by IFN-γ and IL-17A from Th1 and Th17 cells, respectively, whereas UC is mediated by IL-4 and IL-13 from Th2 cells [1]. Consistent with the ndings in mice with DSS-induced acute colitis [29,30,31], the mRNA expression of IL-17 in the splenocytes and the mRNA expression of IFN-γ and IL-17 in the colon increased in the DSS and DSS/PBS groups. However, SJMHE1 treatment reduced the mRNA expression levels of IFN-γ and IL-17, increased the mRNA expression levels of IL-4 and TGF-β in the splenocytes, and increased the mRNA expression levels of IL-4, IL-10, TGF-β, and IL-35 in the colon of mice.…”
Section: Discussionmentioning
confidence: 58%
“…CD is dominated by IFN-γ and IL-17A from Th1 and Th17 cells, respectively, whereas UC is mediated by IL-4 and IL-13 from Th2 cells [1]. Consistent with the ndings in mice with DSS-induced acute colitis [29,30,31], the mRNA expression of IL-17 in the splenocytes and the mRNA expression of IFN-γ and IL-17 in the colon increased in the DSS and DSS/PBS groups. However, SJMHE1 treatment reduced the mRNA expression levels of IFN-γ and IL-17, increased the mRNA expression levels of IL-4 and TGF-β in the splenocytes, and increased the mRNA expression levels of IL-4, IL-10, TGF-β, and IL-35 in the colon of mice.…”
Section: Discussionmentioning
confidence: 58%
“…This study showed good significant correlations between FSS and other variables (fatigue VAS, BDI, BEPSI-K, EQ-5D-3L, and EQ-VAS) at baseline and 8 weeks later. These correlations indicate that the participants’ responses to the questionnaire in the two groups are reliable ( 34 ). Nevertheless, contrary to expectations, daily intake of fermented PV for 8 weeks did not show a more remarkable effect than that of placebo on FSS, fatigue VAS, BDI, BEPSI-K, EQ-5D-3L, EQ-VAS, lactate, CK, and MDA concentrations in adults with unexplained fatigue.…”
Section: Discussionmentioning
confidence: 88%
“… Isas et al (2023) showed that fermented pomegranate juice could ameliorate hyperglycemia, hyperlipidemia, fat deposition, and hepatic tissue damage in high-fat diet-induced obese C57BL/6 mice through its antioxidant activity. Kim et al (2021) demonstrated that fermented plums of L. plantarum and L. casei were effective in reducing the risk of cancer via inhibiting oxidative stress and the expressions of pro-inflammatory factors including TNF-α, IL-1β, IL-6, IL-12, and IL-17 in DSS-induced colitis mice.…”
Section: The Beneficial Effect Of Fruit Fermentationmentioning
confidence: 99%